Stopping power of heavy particles in a partially ionized aluminum plasma - Kodanova, S.K.; Abdimanapova, M.A. (Recent Contributions to Physics, 2012)
In this paper we investigate the stopping power of heavy particles in a partially ionized plasma. The value of the Coulomb logarithm is most accurately determined using the pseudopotential taking into account the effect of screening at long distances. The obtained values of the Coulomb logarithm depending on the temperature of the plasma are compared with experimental data and with results of other authors.